Integrating Anti-Corruption Values into Islamic Education: A Character-Based Framework for Ethical Citizenship in Turkey - Gunbay (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Corruption remains a persistent challenge that undermines social justice, public trust, democratic governance, and sustainable development across many societies. In response to these challenges, educational institutions play a crucial role in fostering ethical awareness and preventing corrupt behavior through character formation and value-based learning. This study explores the integration of anti-corruption values into Islamic education as a character-based framework for developing ethical citizenship in Turkey. Drawing upon the principles of Islamic ethics, character education, and civic responsibility, the study examines how values such as honesty, integrity, accountability, justice, discipline, responsibility, and social concern can be incorporated into educational practices to cultivate morally responsible citizens. Using a qualitative library research approach, data were collected from academic literature, policy documents, educational reports, and relevant studies on Islamic education and anti-corruption initiatives. The findings indicate that Islamic education provides a strong moral and spiritual foundation for promoting anti-corruption attitudes through the internalization of ethical values rooted in the Qur'an and Sunnah. Furthermore, character-based educational approaches encourage students to develop critical moral reasoning, social responsibility, and commitment to public welfare. The study also reveals that the integration of anti-corruption values is most effective when supported by curriculum development, teacher role modeling, institutional culture, and community engagement. In the Turkish context, where Islamic educational traditions continue to influence moral development and citizenship education, the incorporation of anti-corruption principles can contribute significantly to strengthening ethical citizenship and fostering a culture of integrity among younger generations. This study offers a conceptual framework that links Islamic education, character development, and anti-corruption education as complementary strategies for building ethical and responsible citizens in contemporary society.